MANAGEMENT OF OYSTER MUSHROOM CULTIVATION AND WASTE TREATMENT THROUGH THE CIRCULAR ECONOMY MODEL ANALYSIS APPROACH (CASE: MUSHROOM FARMER ASCOCIATION IN JAMBUDIPA DAN PAKUHAJI VILLAGE, CISARUA SUB-DISTRICT, WEST BANDUNG DISTRICT) - Triyafi, Ahmad
Oyster mushroom production in Indonesia, especially in West Java Province, shows an increasing trend every year. The increase in production will cause the problem of hoarding used media waste. Used media waste is still valuable because it has a high organic content and its ability to improve soil structure so that it can be processed as compost, planting media, and also mixed in making new media. This study aims to determine the performance of mushroom cultivation, the financial feasibility of mushroom cultivation, and an economically feasible waste treatment model and to calculate the additional benefits of waste utilization through the Circular Economic Model approach for farmers in Jambudipa and Pakuhaji Villages, Cisarua District, West Bandung Regency. Based on observations it is known that the eight sample farmers have a biological efficiency value of 45-55% with a failure rate of 0.5-25%. At the selling price of mushrooms Rp.6500 / kg, only 4 out of 8 farmers were declared financially viable, seen from the IRR value of 12- 15%, the NPV was positive for 4 farmers, and the payback period was 8 to over 15 years. At the selling price of mushrooms of IDR 11,000 / kg, all farmers are declared financially feasible seen from the IRR value of 38-76%, the NPV is positive, and the Payback Period is 2 to 4 years Farmers have a good achievement indicator value of around 88% up to 92%. There are nine criteria that are considered in determining the method of waste treatment. Based on the analysis of multiple criteria decision analysis with the Analytical hierarchy process method, the two top criteria were obtained, namely the distribution of results and market prospects of the waste treatment. The waste treatment method with the highest performance value against the nine criteria being considered is the processing of baglog waste into planting media. The financial feasibility of processing baglog waste into a viable planting medium for small scale farmers with a production of 1000 baglog per batch and medium to large scale farmers with a production of 2000 baglog and above per batch.